(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was undertaken to analyze the effect of isolated and combined effect of core exercises program and yoga practice on muscular endurance among physical education students. The investigator has selected N=48 male physical education students were selected from Faculty of Physical Education and Yoga, ICFAI University, Tripura, India and their age range from eighteen to twenty five years as per their college record. The selected physical education students for the study were divided into four equal groups n=15 and designated as experimental group ‘A’ experimental group ‘B’ experimental group ‘C’ and control group ‘D’. Core exercises training were given to group ‘A’ yoga practice were given to group ‘B’, Combined training of core exercises and yoga practice were given to group ‘C’ and the ‘CG’ control group ‘D’ were restricted to participate in any activities apart from their curriculum activities. The trainings were given for a period of twelve weeks. The data were collected before and after the training period by conducting bent knee sit ups test. The obtained data’s were analyzed by Analysis of Covariance (ANCOVA). The level of significant was fixed at 0.05 levels. The results of the study showed that core exercises, yoga practices and combined training significantly improved muscular endurance performance level of the physical education students when comparative with control group.